Applied managing for entrepreneurship - Amedzro St-Hilaire, Walter (Burlington, ON, Canada ; Palm Bay, Florida, USA : Apple Academic Press, 2021)
""Applied managing'' has made significant progress. Long assimilated into business economy, business administration, and marketing, the discipline has become indispensable for the adaptation of companies. This book presents the analytical and synthetic dimensions of the foundations of entrepreneurship decisions. It provides an overview of the strategies for business optimization. This book will serve as a guide for those who wish to learn about the optimization of management practices, productivity, and market. The author looks at the main mechanisms usually chosen by companies and the important questions they elicit from CEOs. Generic practices are discussed, which are the most frequently used the tools. Optimization in applied management is not based solely on an analysis of the business context and the resources of the organization. The choices suggested by the context and the capabilities of the organization must also be taken into account as well as the values of the organization, management preferences, and corporate social responsibility. For this reason, various aspects of the complexity of organizations are taken into account in the book. Applied Managing for Entrepreneurship focuses also on the optimization of diversified and internationalized companies. It discusses the reasons for companies to diversify their activities and the various existing optimization mechanisms. Subsequently, the book addresses the challenges associated with applied governing and the strategies that can be used in a globalized context. Managers and academics will find in this book methods and tools that will allow them to analyze the business context and the skills of their organization in order to make relevant choices. This volume also presents the factors that influence the achievement of an operational decision, namely management structure and processes, culture, and leadership. Finally, the book shows how an operational approach often consists of managing the complexity associated with the diversification and globalization of organization and the many changes they experience"--
The Concept of Entrepreneurship -- Business Optimization -- Approaches for Applied Management -- The Foundations of Governance Strategies -- Principles of Corporate Optimization -- Operational Context in Applied Management -- Advanced Operational Business Analysis -- The Implementation of Business Optimization Mechanisms -- Operational Decision-Making -- Applied Operational Analysis -- Optimizing Operational Choicess -- Structures and processes of Applied Management -- Operational Values for Management Optimization -- Metadata and the Complexity Mechanisms -- Optimizing Business Diversification -- Optimization of Business Diversification -- Optimizing Global Business.
OCLC-licensed vendor bibliographic record.
Keywords: Business planning; Entrepreneurship -- Management; Industrial management; BUSINESS & ECONOMICS / Decision-Making & Problem Solving; BUSINESS & ECONOMICS / Entrepreneurship; BUSINESS & ECONOMICS / Management Science